MEMAKSIMALKAN DUKUNGAN KELUARGA GUNA MENINGKATKAN KUALITAS HIDUP PASIEN DIABETES MELLITUS - Rina Mirza (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2017)
ABSTRACT Diabetes Millitus (DM) is one of the most common diseases in Indonesia. In addition to the drugs that must be consumed regularly every day, family support is also needed so that the patient with diabetes is maintained quality of life. Family support is not just how families pay attention to the person with DM, but more than that is serve him sincerely and understand more about DM disease itself. This paper is intentionally made so that families who have relatives who suffer DM more understand what DM is and more can provide full support for DM patients themselves so that the quality of life of patients with DM can increase. Keywords: Diabetes Millitus Patient, quality of life, family support